Micromonospora profundi TRM 95458 converts glycerol to a new osmotic compound - Lu, Di; Shen, Hong-ling; Wang, Lei; Wan, Chuan-xing (Frontiers in Microbiology, 2023)
Plant growth and agricultural productivity was greatly limited by soil salinity and alkalization. The application of salt-tolerant rhizobacteria could effectively improve plant tolerance to saline-alkali stress. Micromonospora profundi TRM 95458 was obtained from the rhizosphere of chickpea (Cicer arietinum L.) as a moderate salttolerant rhizobacteria. A new osmotic compound (ABAGG) was isolated from the fermentation broth of M. profundi TRM 95458. The chemical structure of the new compound was elucidated by analyzing nuclear magnetic resonance (NMR) and highresolution mass (HRMS) data. M. profundi TRM 95458 could convert glycerol into ABAGG. The accumulation of ABAGG varied depending on the amount of glycerol and glycine added to the fermentation medium. In addition, the concentration of NaCl affected the ABAGG content obviously. The highest yield of ABAGG was observed when the salt content of the fermentation medium was 10 g/L. The study indicated that salt stress led to the accumulation of ABAGG using glycerol and glycine as substrates, suggesting ABAGG might aid in the survival and adaptation of the strain in salinealkaline environments as a new osmotic compound.